2003
DOI: 10.1002/jsfa.1339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment and evaporation on patulin and some other properties of apple juice

Abstract: Patulin, hydroxymethylfurfural (HMF), colour and clarity values of 20 apple juice samples with different Brix contents were determined after heat treatment (90 and 100°C for 5, 10, 15 and 20 min under atmospheric pressure) and evaporation (70 and 80°C for 5, 10, 15 and 20 min) processes. As the heating and evaporation times increased, the concentration of patulin in the apple juice samples decreased. The 90 and 100°C heat treatments resulted in reductions in patulin concentration of 18.81 and 25.99% respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 5 publications
3
44
2
Order By: Relevance
“…PAT did not follow this trend because its disappearance was not primarily due to adsorption, but to hydrolysis or pyrolysis. The reported decrease of PAT in apple juice after pasteurization 25,26) suggests a possibility of PAT was decomposed during mashing.…”
Section: <3:6mentioning
confidence: 98%
“…PAT did not follow this trend because its disappearance was not primarily due to adsorption, but to hydrolysis or pyrolysis. The reported decrease of PAT in apple juice after pasteurization 25,26) suggests a possibility of PAT was decomposed during mashing.…”
Section: <3:6mentioning
confidence: 98%
“…Brackett and Marth 2 , using Sorensen's phosphate buffer at 25°C, found the half-life of PAT to be 64 h at pH 8 versus 1310 h at pH 6 (apparent 1st-order reaction). Therefore, heat treatment (pasteurization) and storage cannot completely inactivate PAT in apple juice or ciders 9,10 . Kadakal and Nas 10 report, however, that thermal treatment of apple juice at 100°C for 20 min followed by evaporation leads to 30% degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, heat treatment (pasteurization) and storage cannot completely inactivate PAT in apple juice or ciders 9,10 . Kadakal and Nas 10 report, however, that thermal treatment of apple juice at 100°C for 20 min followed by evaporation leads to 30% degradation. Surprisingly, 4 months of dark storage also appears to decrease (by 50%) the PAT level in apple juice 1 .…”
Section: Introductionmentioning
confidence: 99%
“…During distillation however there is the possibility that PAT can be transformed in volatile substances that are distilled away. Kadakal and Nas reported that evaporation for 20 minutes at 70°C reduced the level of the PAT by 9.4% and using a temperature of 80°C the levels are reduced by 14% [85].…”
Section: Patulinmentioning
confidence: 99%
“…Many studies have been realized combining different approaches, for example the centrifugation and the use of the refined bentonite are able to reduce the level of the PAT of 21%, while the combination of centrifugation and the treatment by pectinase reduces the level of the PAT of 17% [84]. Kadakal and Nas (2003) reported the treatment of apple juices at 90°C and 100°C for 20 min observing the reduction of PAT level of 19% and 26%, respectively [85]. Raiola et al simulated an industrial thermal treatment in artificially spiked apple purees and apple juices, observing an average loss of 1.41% and 62.62% respectively [86].…”
Section: Patulinmentioning
confidence: 99%